Peer‐related loneliness across early to late adolescence: Normative trends, intra‐individual trajectories, and links with depressive symptoms. Issue 6 (17th June 2013) - Ladd, Gary W.; Ettekal, Idean
Abstract: Study aims were to: (a) describe normative levels and person‐oriented developmental trends in loneliness across adolescence, and (2) examine the association between loneliness and depressive symptoms during this same epoch. Participants included 478 youth (239 males and females; 80% Caucasian, 16% African American, and 4% other). Measures of loneliness and multiple indicators of depressive symptoms were gathered yearly across grades 6 through 12 (ages 12–18). Findings implied that most adolescents experience loneliness more strongly during early rather than later adolescence, but not all adolescents traverse the same loneliness trajectories. Youth followed one of five distinct trajectories, characterized as: (a) stable non‐lonely, (b) stable low lonely, (c) stable high (chronic) lonely, (d) moderate decliners, and (e) steep decliners. Adolescents following stable high and moderate loneliness trajectories displayed the most depressive symptoms and, although informant differences were found, these youth also manifest the largest gains in depressive symptoms over time.